Interval-valued fuzzy ku-ideals of ku-algebras - Muhammad Akram, Muhammad Akram; Yaqoob, Naveed; Kavikumar, Jacob (Academic Publications, Ltd., 2014)
In this paper, we introduced the notion of interval-valued fuzzy KU-ideals of KU-algebras and some related properties are investigated. We proved that U is a KU-ideal if and only if the interval-valued fuzzy subset is an interval-valued fuzzy KU-ideal of a KU-algebra for e-e